Child Grooming Sebagai Bentuk Pelecehan Seksual Anak Melalui Aplikasi Permainan Daring - Anna Maria Salamor; Astuti Nur Fadillah Mahmud; Patrick Corputty; Yonna Beatrix Salamor (Faculty of Law, Universitas Pattimura, 2020)
The rapid development of society and the development of technological advancements with the use of the internet in addition to having a positive impact can also have an impact with increasing crime that appears With a variety of modus operandi based on technological tools that if not accompanied by the development of knowledge in society about the law will cause a person to become a criminal or being a victim of a criminal offense is not uncommon for children to be targeted as victims. One form of crime that occurs in society is the crime of sexual abuse of children through the internet so that the development of the rule of law is also demanded to be able to overcome the development of this problem. This study aims to assess and analyze whether child grooming can qualify as a form of sexual abuse against children. The method used in this study is normative juridical. The results obtained show that child grooming in Hago games through online media is done with the victim mode being asked to send photos or videos without using clothes or naked by the groomer. Groomer builds closeness with the initial mode of asking for the victim's wa number and establishing closeness, giving rise to sympathy and empathy so that closeness is established between the victim and the perpetrator.